A systematic review of social media as a teaching and learning tool in higher education: A theoretical grounding perspective - Mc Guckin, Conor (My University, 2023)
The use of social media in higher education has been demonstrated in a number of studies to be an attractive and contemporary method of teaching and learning. However, further research and investigation are required in order to align social media’s pedagogical benefits with the theoretical perspectives that inform educational practices. It is the objective of this study to provide a systematic literature review using bibliometric analysis techniques and content analysis to provide a map of research produced between 2009 and 2021. This study aims to identify theoretical frameworks, current research trends, and patterns in this field. A total of 772 publications were analysed using bibliometric methodology, while a subset of 55 publications were analysed using content analysis. As indicated by the results, there is still a growing interest in this area of research, with recent studies still focusing on attitudes towards the use of social media in teaching and learning. According to the content analysis, technology acceptance theories and learning theories are the most commonly used reference theories. This field has yet to elaborate on pedagogical theory, and there is a tendency to rely primarily on technology acceptance models rather than pedagogical models. A discussion of future practice and research implications is also provided.
PUBLISHED
Keywords: Social media; Teaching; Learning; · Systematic review; Higher education